City of secrets - Tracy, P. J. (Tracy, P. J. Detective Margaret Nolan series, 2024)
"Los Angeles Police Detective Margaret Nolan and her partner have worked a lot of different cases, ones where things aren't always as they appear. And it's Nolan's job to find the truth in the darkness around her. When they're called to the scene of what looks like a fatal car-jacking, Nolan soon realizes her victim was a founder of a company about to sell for millions, and within a day of his death, his partner's wife is abducted. As Nolan learns more about the victim and his life, she gets pulled into a disturbing world of sex, violence, and big business; and an even darker world, where whispers of an "Angel of Death" are beginning to surface. One of today's finest crime writers, P. J. Tracy has created a series that is a rich and authentic portrait of LA, filled with the tragedy and optimism of her multi-layered characters and a story guaranteed to keep readers enthralled"--